Libraries for Sustainable Development: Vision and Action - Alenzuela, Reysa (Nazarbayev University, 2017)
Libraries are not just spaces; these are places for advocacy— the stirrers of intellectual conversations and thoughtful engagement. Increased access to information and knowledge across society, assisted by the availability of information and communications technologies (ICTs), supports sustainable development and improves people’s lives. This paper provides an overview on the role of libraries in promoting the United Nations 2030 Agenda. It also provides is a brief introduction on how libraries can drive progress across the 17 sustainable development goals. Although public libraries are at the forefront of this endeavor, sustainable development is a global concern that involves even academic libraries.
Keywords: library advocacy; sustainable development; United Nations 2030 Agenda; public library; academic library; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science